The Improvement of Productivity and Benefits for Farmers: Analysis of Production Factors, Social Capital, and Demography - Dian Ayu Novia; Dwi Retno Andriani; Rosihan Asmara (The University of Lampung, 2025)
This study aims to analyze the influence of production factors, social capital, and socio-demographic on the productivity and welfare of farmers in Klampok Village, Kapas District, Bojonegoro Regency. Utilizing a quantitative method with a likert scale for measuring variables, the research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. Data was collected from 52 respondents determined based on the total farming population in Klampok Village, ensuring statistical adequacy for analysis. The findings indicate that production factors, social capital, and socio-demographic variables significantly impact both the productivity and welfare of farmers. The highest mean value was found for experience variable, suggesting a high level of respondent agreement. Conversely, income variable recorded the lowest mean value but within a satisfactory range. The study contributes to the understanding of how these factors collectively enhance farmers' living standards, with productivity serving as a moderating variable in achieving welfare. The research underscores the importance of optimizing production factors, social capital, and demographic aspects through policy development and program implementation to improve farmers' welfare. The results are expected to inform policymakers, agricultural practitioners, and the community about the critical factors enhancing the livelihood of farmers, and program implementation to improve farmers' welfare. Keywords: Farmer’s Welfare, Production Factors, Productivity, Social Capital, Socio-Demographic Factors.